The Development of an Ethnoscience-Based Mangrove Module in Improving Student’s Critical Thinking Abilities and Concern for the Environment at SMA IT Daarul Hikmah Bontang - Sri Roma Yuliarta; Muhammad Amir Masruhim; Aloysius Hardoko; Krishna Purnawan Candra; Sukartiningsih; Taufan Purwokusumaning Daru; Elsje Theodore Massawet; Masitah; Yusak Hudiyono (Postgraduate, University of Mataram, 2024)
A module is an educational material or learning tool that includes teaching materials, methods, and assessments that are developed in a systematic and structured manner to achieve expected competency goals. The aim of this study is to develop a valid, practical and effective mangrove module based on ethnoscience on biodiversity. The type of research is R&D which refers to the ADDIE method developed by Mayfield. Data collection techniques consist of expert verification, observations, tests, questionnaires, and interviews. The results of the study show that, this module was developed based on the manual previously used by SMA IT Darul Hikmah Bontang students to learn biology. The module validity result for the module is 99%, which is in the very valid category. The material validity result of the module was in the very reasonable category at 84.69%. The linguistic validity result of the module was 73.6% in the valid category. The results of the student survey regarding the practicality of the module were 88.65%, which fell into the very practical category. The effectiveness module in improving student’s critical thinking ability and environmental awareness have n-gain values ​​are 0.55 and 0.44. It can be concluded that the development of the ethnoscience-based mangrove module in the intermediate category has been effectively used to improve the critical thinking skills of the students of SMA IT Darul Hikmah Bontang.